Pengaruh Media Spindle Boxes Terhadap Kemampuan Berhitung Anak - batubara, lailatussipah; Ismet, Syahrul; Marlina, Serli (Universitas Negeri Padang, 2019)
This article describes the results of the effect of stripboard media on the ability of counting children aged 5-6 years in Taman Kanak-kanak Darul Falah Padang. Counting activities in children still use an abstract magazine without being combined with the media. So the child becomes bored, saturated and not interested in following the learning activities. Through this research developed a learning media strip board to ability to count children. This study uses an experimental quasy approach with the number of children of kindergarden Anggrek as many as 48children. The sample B4 control class and the experimental class B3 were each 10 children with saturated sampling technique. The results showed that the average of experiment class is 87,5 and control class is 71,88. The research findings that media spindle boxes can develop the ability to count children in learning activities.